Pemilu dan Korupsi: Fenomena Pelanggaran Etika dan Moral Penyelenggara Pemilu di Indonesia - Pandu Alfa; Khairul Fahmi (Pencerah, 2022)
Corruption is defined as a form of misappropriation or misappropriation of state money, including companies, organizations, foundations, and so on for personal gain or others. The use of morals and ethics is not optimal, so this study aims to explain morals and ethics to prevent political corruption during elections especially among election organizers. This study uses a qualitative approach with a descriptive method using secondary data sources such as journals and books. The results of the study show that there are still public officials and election administrators who have problems with integrity such as vote buying, individual gifts, services and activities. The conclusion of this study shows that, election fraud arises like money politics, candidacy buying, electoral administrative corruption, abusive donation, it is necessary to have strict supervision so that the escalation of electoral conflict can be avoided.